Baby-Led-Weaning (BLW) from maternal perspective: Polish experience - Poniedziałek, Barbara; Paszkowiak, Natalia; Rzymski, Piotr (Journal of Medical Science, 2018)
Background. Baby-Led-Weaning (BLW) is increasingly popular as a complementary feeding practice although its safety, limitations and advantages have not been widely studied as yet. Material and Methods. The present survey employed an anonymous online questionnaire to learn from experience (their concerns, perceived advantages, disadvantages, and overall satisfaction) of Polish mothers (n = 373) that adopted BLW. Results. Most of surveyed mothers adopting BLW had tertiary education and good economic status, and inhabited urban areas. Non-scientific online resources were the most important source of knowledge on BLW; none of surveyed mentioned healthcare professionals as having played any role in this respect. The risk of choking was the greatest concern expressed while considering the BLW prospect. At least one choking event during B:W adoption was reported by 55.6%, mostly involving an apple, occurring at beginning of introduction, and perceived as non-serious. The BLW advantages included: (i) promotion of infant self-reliance, motor skills, biting and chewing of food and speech), sensory learning of food, and (ii) motivation to eat family meals and make more healthier dietary choices. The greatest disadvantage was an in-house mess. Nearly all mothers recommended the BLW adoption to other caregivers. Conclusion. In view of the scarcity of data on this feeding practice, the maternal experience demonstrated in the present study may offer valuable information for health professionals as well as future caregivers who consider the adoption of BLW to be a complementary feeding practice.